The Effect of the Problem-Based Learning (PBL) Model on Elementary School Students’ Motivation in Physical Education - Iyan Iyan; Usman Usman (Darul Yasin Al Sys, 2026)
Although the issue of low learning motivation in Physical Education at the elementary school level has received increasing attention in prior studies, research specifically examining the application of Problem-Based Learning (PBL) to enhance students’ motivation in Islamic elementary school contexts remains limited. This study aims to analyze the effect of the PBL model on the learning motivation of elementary school students in Penjas learning. A quantitative approach was employed using a quasi-experimental nonequivalent control group design involving 40 fifth-grade students at MIS Muhammadiyah Parepare, selected through purposive sampling, with the study conducted in November 2025. Data were collected using a validated learning motivation questionnaire and classroom observation sheets, and analyzed using descriptive statistics and an independent samples t-test. The findings indicate a statistically significant difference between the experimental and control groups (p < 0.05), where students taught using the PBL model demonstrated higher motivation scores than those taught through conventional methods. These results contribute to the theoretical development of constructivist learning theory and broaden understanding of student-centered learning implementation in Physical Education at the elementary level, particularly within Islamic school settings. The study concludes that the PBL model plays a crucial role in increasing students’ learning motivation in Physical Education and recommends that teachers adopt PBL as an innovative instructional strategy in Penjas learning. The implications include theoretical contributions to the growing literature on active learning models and practical recommendations for schools and educators to integrate problem-based approaches into Physical Education instruction. Furthermore, the study highlights opportunities for future research on the long-term effects of PBL on students’ affective and psychomotor outcomes in elementary Physical Education.